Effectiveness of the Auditory Temporal Ordering and Resolution Tests to Detect Central Auditory Processing Disorder in Adults With Evidence of Brain Pathology: A Systematic Review and Meta-Analysis - Chowsilpa, Sanathorn; Bamiou, Doris-Eva; Koohi, Nehzat (Frontiers in Neurology, 2021)
Background: Auditory temporal processing tests are key clinical measures in order to diagnose central auditory processing disorder (CAPD). Although these tests have been used for decades, there is no up-to-date evidence to determine the effectiveness of detecting the abnormalities in central auditory processing in adults while the available national CAPD guidelines predominantly address CAPD in the pediatric population. Purpose: To determine the efficacy of the auditory temporal ordering tests, duration pattern test (DPT) and frequency pattern test (FPT), and a temporal resolution test, gaps-in-noise (GIN) test, for detecting the central auditory processing abnormalities in adults with documented brain pathology. Research Design: Systematic reviews and meta-analyses. Study samples: Four databases, including PubMed, Web of Science, EMBASE, and Scopus, were systematically searched. The publications in the English language, that recruited adults (above 16-year-old) with pathologic brain conditions and described the diagnostic tests for auditory temporal processing, were selected for reviews. Data Collections and Analysis: All data were systematically evaluated, extracted, categorized, and summarized in tables. The meta-analysis was done in order to determine the effectiveness of the DPT, FPT, and GIN tests. Results: The results showed significantly poorer performance of DPT and FPT, compared between participants with confirmed brain disease and normal controls, at the mean differences of percent correct -21.93 (95% CI, -26.58 to -17.29) and -31.37 (95% CI, -40.55 to -22.19), respectively. Subjects with brain pathology also performed poorer in GIN test at the mean difference of 2.79 milliseconds (95% CI, 2.33 to 3.25). Conclusion: The results from the meta-analysis provide evidence that DPT, FPT, and GIN clinical measures are effective in diagnosis of CAPD in adults with neurological disorders. Poor performance on these tests is significantly related to the confirmed brain pathology. However, different units in results presentation and variety of testing strategies are limitations for this meta-analyses. The standard pattern of result reporting and international protocols test strategies should be developed in order to conduct better meta-analyses with a larger collection of suitable studies and less heterogeneity.